2016
DOI: 10.1007/s10508-016-0698-2
|View full text |Cite
|
Sign up to set email alerts
|

Geosocial Networking App Use Among Men Who Have Sex With Men in Serious Romantic Relationships

Abstract: Geosocial networking (GSN) mobile phone applications (“apps”) are used frequently among men who have sex with men (MSM) to socialize and meet sexual partners. Though GSN apps are used by some MSM in partnered relationships, little is known about how the use of GSN apps among MSM in serious romantic relationships can influence couples' sexual and relationship health. MSM in serious relationships (N = 323; M age = 40 years) were recruited through a popular GSN app for MSM. Participants completed open-ended items… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
23
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 26 publications
0
23
0
Order By: Relevance
“…Unsurprisingly, participants reported that these were predominantly one-time sexual encounters or recurring hookups, yet many reported having other types of relationships with app-met partners, including friendships or serious relationships. Among adult GBQ-app users, it is routine for such apps to facilitate the development of other types of relationships, such as sexual relationships that later evolve into friendships or serious partnerships (Gudelunas, 2012;Holloway et al, 2014;Macapagal et al, 2016). For SGM AMAB adolescents, however, who are less likely to be out about their sexual orientation identity and may lack access to other SGM peers and potential partners where they live, sexual networking applications have the potential to contribute to a sense of belonging and social support similar to other online spaces and social media (Craig & McInroy, 2014;Harper et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unsurprisingly, participants reported that these were predominantly one-time sexual encounters or recurring hookups, yet many reported having other types of relationships with app-met partners, including friendships or serious relationships. Among adult GBQ-app users, it is routine for such apps to facilitate the development of other types of relationships, such as sexual relationships that later evolve into friendships or serious partnerships (Gudelunas, 2012;Holloway et al, 2014;Macapagal et al, 2016). For SGM AMAB adolescents, however, who are less likely to be out about their sexual orientation identity and may lack access to other SGM peers and potential partners where they live, sexual networking applications have the potential to contribute to a sense of belonging and social support similar to other online spaces and social media (Craig & McInroy, 2014;Harper et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The introduction of geosocial networking (GSN) smartphone applications ("apps") in the last decade has facilitated sexual partner seeking among sexual minority male adults in the U.S. (Goedel & Duncan, 2015;Paz-Bailey et al, 2017) and worldwide (Choi, Wong, & Fong, 2017;Krishnan et al, 2018;Lorimer, Flowers, Davis, & Frankis, 2016;Luo et al, 2019). These technologies allow users to explore sexual desires, meet sexual needs, and connect to the gay community (Holloway et al, 2014;Macapagal, Coventry, Puckett, Phillips, & Mustanski, 2016;Van De Wiele & Tong, 2014). GSN app use has been associated with greater engagement in sexual health services such as HIV testing among sexual minority men (Krishnan et al, 2018;Landovitz et al, 2013;Lorimer et al, 2016;Rendina, Jimenez, Grov, Ventuneac, & Parsons, 2014).…”
mentioning
confidence: 99%
“…Meanwhile, online dating has now become more popular among gay community because of its ease of access, anonymity and high acceptability [5355], especially in young groups[56]. Pilot studies suggested that men who had sex with an online partner were at higher risk for contracting HIV and STIs compared to those who did not approaching partners online[53,57,58]. Some previous studies revealed that, the majority of gay men prefer receiving AIDS related intervention via internet rather than via CDC or hospitals due to the anonymous nature of the social media[8,59].…”
Section: Discussionmentioning
confidence: 99%
“…Previous research on app use among GBQT2+ indicates that dating applications provide a means of engaging in romantic, sexual and interpersonal relationships, including casual sexual encounters [9][10][11][12][13]. As well, these apps are tools that help address issues of mental health, internalized homophobia and low self-esteem [14].…”
Section: Introductionmentioning
confidence: 99%